ZPT Test and Rootone-F Against for Cuttings of Premna serratifolia L. - Okky Feri Ananda; Antar Sofyan; Ronny Mulyawan (Warmadewa University Press, 2022)
Green grass jelly (Premna serratifolia L.) is a vine or coiled plant originating from Southeast Asia. Green grass jelly cultivation in Indonesia is still relatively low due to the difficulty of cultivating grass jelly plants, especially in terms of plant propagation. In general, propagation is done by stem cuttings. PGR that is often used is synthetic ZPT, one of which is Rootone F, but its use is less effective in terms of economy. it is necessary to substitute with ZPT derived from natural materials or from the use of household and industrial wastes such as coconut water, rice washing water, and tofu waste water. The purpose of this study was to determine the effect of soaking natural PGR in coconut water, rice washing water, and tofu waste water and to find out the best natural PGR ingredients for the growth of green grass jelly plants. This study used an experimental design used was a one-factor Completely Randomized Design (CRD), which consisted of four treatments and was repeated five times so that twenty experimental units were obtained with 3 samples each, requiring 60 plants. P1=0.1 gL-1 Rootone F (positive control), P2=450 ml.L-1 young coconut water, P3=450 ml.L-1 rice washing water, P4=450 ml.L-1 tofu dregs water.